PENGARUH KONSENTRASI EKSTRAK DAUN KEPEL (Stelechocarpus burahol (BL) Hook f. & Th.) TERHADAP AKTIVITAS ANTIOKSIDAN DAN SIFAT FISIK SEDIAAN KRIM - Anita Oktaviani Suwandi; Suwidjiyo Pramono; Mufrod Mufrod (Faculty of Pharmacy, Universitas Gadjah Mada, 2012)
This research was aimed to determine the effect of concentrations of Kepel leaves’ (Stelechocarpus burahol (BL) Hook f. & Th.)extract to antioxidant activity and physical properties of cream. Kepel leaves’ extract were made by infundation method. The antioxidant activity was tested by DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging method. Cream was made in three formulas with variation concentrations of Kepel leaves’ extract (2,5; 5,0; 7,5%b/b) using w/o basis. Physical stability parameters tested in this research were homogenity, dispersive power, adhesion, and viscosity. Data were then analyzed statistically by ANOVA One Way and Turkey Test at 95% level of significance. The results showed that concentration of Kepel leaves’ extract as an active ingredient cause different color, odor, and viscosity of the cream. The concentrationdifference of Kepel Leaves’ extract as an active ingredient was not affected the homogenity, adhesion, and the separation ratio of the cream. The difference concentration was not cause affected daya sebar cream unless the formula II (5.0% w/w) and formula III (7.5% w/w). Increasing concentration of Kepel leaves’ extract caused a different antioxidant activity unless the formula II (5.0% w/w) and formula III (7.5% w/w).